Phosphatase activities and available nutrients in soil aggregates affected by straw returning to a calcareous soil under the maize–wheat cropping system - Lin, Xiang-Jie; Zhang, Guang-Na; Wang, Zhen; Han, Qing-Dian; Leng, Peng (Frontiers in Environmental Science, 2023)
The objective of this study was to investigate the effects of different rates of straw returning on soil aggregate stability, phosphatase activities, and the available nitrogen (N) and phosphorus (P) within different soil aggregate sizes. The experiment included five treatments: 1) no straw returning and no chemical fertilizer, 2) chemical fertilizer only (150 kg N ha -1 ，75 kg P ha -1 ，75 kg K ha -1 ), 3) 20% straw returning with chemical fertilizer, 4) 60% straw returning with chemical fertilizer, and 5) 100% straw returning with chemical fertilizer. Soil samples were collected 3.5 years after the start of the experiment and separated into four aggregate sizes (< 0.25mm, 0.25-1mm, 1-2mm, and 2-7 mm) using the dry sieving method. Soil acid (AcP) and alkaline phosphomonoesterase (AlP), phosphodiesterase (PD), pyrophosphatase (PrA) activities, and soil NO3 − −N, NH4 + −N, and resin-P were determined within soil aggregates. The results showed that straw returning rates did not significantly impact soil aggregate distribution. However, straw returning increased soil AcP, AlP, and PD in < 2 mm aggregates, and high rates of straw returning led to high enzyme activities. Soil phosphatase activities were also higher in 1-2 mm aggregates. All straw returning and chemical fertilization treatments increased soil NO3 − −N and resin-P concentrations but had much less effect on soil NH4 + −N concentrations. Additionally, the study revealed that soil pH, the concentrations of NH4 + −N, NO3 − −N, resin-P, and CaCO3 significant influenced soil phosphatase activities, but their impact varied across different sizes of aggregates.